A dancer and a cymbal player on the wall of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The depicted image is of the jangha (wall), and garbhagriha (sanctum sanctorum) of the Undeshwar Temple features a dancer and a cymbal player, both shown from the rear with their upper bodies twisted towards the viewer. One of their arms is raised while the other is lowered. The dancer is making classical dance gestures, while the cymbal player holds cymbals in both hands. They possess voluptuous figures, and their beauty is accentuated by their ornate jewelry.